Kontribusi Sikap Disiplin, Fasilitas Belajar, dan Monitoring Orang Tua terhadap Kemandirian dan Dampaknya Pada Hasil Belajar Matematika Siswa Kelas VIII SMP Muhammadiyah 5 Surakarta Tahun Ajaran 2016/2017 - Apriliani, Farida Atma, Prof. Dr. Sutama, M.Pd (2017)
The purposes of research, (1) examine the contribution of the attitude discipline, learning facilities, and monitoring parents on learning outcomes mathematics indirectly through student independence, (2) examine the contribution of the attitude discipline, learning facilities, and monitoring parents of student independence, and (3) examine the contribution of student independence on learning outcomes in mathematics. This type of research is based on a quantitative approach. The study population 163 eighth grade students of SMP Muhammadiyah Surakarta 5. The research sample 116 students is determined by the formula slovin. The sampling technique using proportional random sampling. The data collection technique with questionnaires and documentation. Data were analyzed using path analysis. The results of the study, (1) Attitude Discipline, Learning Facilities, Monitoring Parents contribute simultaneously to the results of Learning Mathematics through Independence with (α = 0.05). Partially, discipline does not contribute directly to the learning outcomes of mathematics and indirectly contribute positively through independence. The learning facilities do not contribute directly to the learning outcomes of mathematics and indirectly contribute positively through independence. Monitoring parents do not contribute either directly or indirectly through the independence of the learning outcomes in mathematics, and (2) Attitude Discipline, Learning Facilities, Monitoring Parents, contributing simultaneously to Independence with (α = 0.05). Partially, the discipline that directly affect the independence of 4.2849%. Learning facilities which directly affect the independence of 16.7281%. Monitoring parents directly affect the independence of 0.0961%. (3) Independence contributes to the learning outcomes of mathematics at (α = 0.05).